Gerakan Shalat Sebagai Implementasi Islamic Center Di Kabupaten Deli Serdang Dengan Tema Arsitektur Metafora - Hilda Mawarni Pohan; Aulia Muflih Nasution; Yunita Syafitri Rambe (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
The number of crime cases in North Sumatra continues to increase, one of the cases in Deli Serdang Regency, namely cases of violence against women and children. The factor is caused by imitating the technology media that is growing rapidly at this time. As a result, morale, morals and behavior are damaged inside. Therefore, to improve morals within oneself, positive activities such as religious activities are needed. For this reason, a container or place is needed that can support religious activities such as an Islamic Center. In the design of the Islamic Center, motivation is needed that can relate that the image of the building can improve bad morals, by imitating the visuals of the building in the form of prayer movements. This has been mentioned in the Al-Quran (QS: Al Ankabut (29: 45))